Evaluasi Jalur Evakuasi Bencana Kebakaran pada Vihara Prajna Chan - Muniifah Zahraani Setio Setoto; Previari Umi Pramesti (Jurnal Sipil dan Arsitektur, 2023)
Vihara is a public building that is used to serve the needs of the general public as a meeting building for worship. Worship buildings must have comfort and security in every situation that can protect the facilities and visitors inside, including in the case of fire disaster rescue. At the Prajna Chan Temple, the fire disaster evacuation routes are still not fully met. Therefore, it is necessary to carry out an evaluation to determine the effectiveness of its use in accordance with the requirements of Minister of Public Works Regulation no. 26 of 2008, SNI 03-1735-2000, SNI 03-1746-2000, and SNI 03-6574-2001. The aim of this research is to determine the suitability of the conditions for the effectiveness of fire disaster evacuation routes in accordance with applicable standards and regulations and to become a more optimal design solution option for the monastery circulation area during the fire disaster evacuation process. The quantitative descriptive method is used as a research method where this method is carried out in several stages, such as through analysis of each component part based on existing standards and regulations. Quantitative data was obtained through the process of literature study, understanding working drawings, and observing data collection at the location. In general, the research results show that the feasibility level for fire disaster evacuation at Prajna Chan Temple only obtained 32% of the 88 requirements. The fulfillment of evacuation routes needs to be reviewed to optimize comfort, safety and smoothness of the evacuation process as a mitigation effort at the Prajna Chan Temple when a fire occurs.